Acidentes graves fatais no trabalho de corte mecanizado de cana-de-açucar: o olhar através do método mapa - Rodrigues, Débora Andreossi [UNESP] (2014)
The growth of the sugarcane industry in Brazil and, specially, in the State of São Paulo, brought up the issue about the safety and health conditions of workers in mechanized cutting of sugarcane plantations. Technical, political and economic factors as well as the prohibition of sugarcane’s straw burning generated, as a consequence, the mechanized harvesting of raw sugarcane. The question that arises is how this activity, associated with the intense pace and almost uninterrupted work hours during a day and with labour conditions, influences the profile of workplace accidents in the sector and in worker’s health conditions, in view of technological and organizational innovations resulting from mechanization. It is intended, with this study of qualitative nature, to understand the reflexes of the mechanization process of the sugarcane fields in the accidents profile from the sugar and alcohol sector; restudy, based in MAPA method (Analysis and Prevention of Accidents Model), five serious or fatal accidents occurred in workfronts of mechanized sugarcane cutting, previously analyzed by Labour Auditors from Work and Employment Ministry and inserted in the Federal Labour Inspection System; recommend, based on the restudies of the five cases realized by the MAPA method, prevention and improvement measures of the health and work conditions of the machine operators and discuss the contributions and limits of using the referred method. In this context, work accidents, related to new risks arising from the process of mechanization of the sugar-alcohol sector, need to be analyzed with the incorporation of modern concepts and methods of analysis, which start from a global analysis of work situations and multi-causal view of accidents. The study has as source of information: a) records and reports from serious and fatal accidents analyzed by Labour Auditors; b) the interviews realized with 30 workers, being machine operators, professionals from ...